2021
DOI: 10.7717/peerj.10911
|View full text |Cite
|
Sign up to set email alerts
|

A community perspective on the concept of marine holobionts: current status, challenges, and future directions

Abstract: Host-microbe interactions play crucial roles in marine ecosystems. However, we still have very little understanding of the mechanisms that govern these relationships, the evolutionary processes that shape them, and their ecological consequences. The holobiont concept is a renewed paradigm in biology that can help to describe and understand these complex systems. It posits that a host and its associated microbiota with which it interacts, form a holobiont, and have to be studied together as a coherent biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 175 publications
0
29
0
Order By: Relevance
“…Although seaweed and oysters do not have direct ecological interactions, they are connected by seawater and share microbes. Our study therefore extends the concept of pathobiome beyond recognized pathogens to other ecosystem components, and contributes to establishing a community perspective of host-pathogen interactions (Dittami et al, 2021). These results are therefore important to better understand the risk of disease in marine ecosystems.…”
Section: Discussionmentioning
confidence: 53%
“…Although seaweed and oysters do not have direct ecological interactions, they are connected by seawater and share microbes. Our study therefore extends the concept of pathobiome beyond recognized pathogens to other ecosystem components, and contributes to establishing a community perspective of host-pathogen interactions (Dittami et al, 2021). These results are therefore important to better understand the risk of disease in marine ecosystems.…”
Section: Discussionmentioning
confidence: 53%
“…Microbiome metrics may be particularly suited to identify and predict large-scale shifts in ecosystem structure and function ( 46 , 50 ). This requires integrating knowledge of how stressors impact hosts, microbes, and host-microbe interactions through time and space ( 51 ), a challenge for aquatic ecosystems, where chemical and microbial diversity—and their dynamics—remain underexplored ( 52 ).…”
Section: Leveraging Cross-system Comparisonsmentioning
confidence: 99%
“…Dr. Not illustrated this claim through an analysis of the most recent research on marine microbiomes, making it clear that, fifty years after the work initiated by Lovelock, our understanding of the marine microbiomes had now turned into a major scientific issue, and that, without explicit consideration of these microbiomes, major biogeochemical cycles impacting the planet, in particular the carbon cycle, could not be properly modeled. Yet, Dr. Not also showed that, while microbial studies were starting to unravel the role of microbes in the functioning of oceanic ecosystems, the functions and interactions of a shockingly large proportion of marine microbial genes and species remained problematically unknown [10][11][12][13]. Finally, Dr. Catherine Larose (CNRSEEA/Ampère, Lyon, France), a microbial ecologist, closed the first session by reflecting on the diversity and the evolution of microbial communities in Polar Regions.…”
Section: A Cross-disciplinary Perspectivementioning
confidence: 99%